2015
DOI: 10.1182/blood.v126.23.1089.1089
|View full text |Cite
|
Sign up to set email alerts
|

Thromboelastographic Evaluation of Coagulation in Patients with Liver Disease

Abstract: Background: Patients with acute and chronic liver disease have long been assumed to have a bleeding tendency on the basis of abnormal results for standard tests of hemostasis. The concept that patients with liver disease are at an increased risk of bleeding, based solely on abnormalities of conventional coagulation tests such as prothrombin time (PT) and international normalized ratio (INR), is now recognized to be an overly simplistic interpretation of an extremely complex situation. Thromboelastography (TEG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…A prospective observational study comparing cirrhotic and noncirrhotic liver disease patients with healthy controls found strong correlations between the platelet count and two TEG parameters (MA and the coagulation index) in all cohorts. 24 However, only weak correlations were seen between INR/PT and TEG parameters R and K (kinetic time), which reflect time to initial clot formation and speed of clot formation, respectively. Another study examining TEG in 270 patients with cirrhosis found that K, α-angle, and MA correlated well with platelet count and fibrinogen in all subgroups, regardless of cirrhosis etiology.…”
Section: Thromboelastographymentioning
confidence: 98%
“…A prospective observational study comparing cirrhotic and noncirrhotic liver disease patients with healthy controls found strong correlations between the platelet count and two TEG parameters (MA and the coagulation index) in all cohorts. 24 However, only weak correlations were seen between INR/PT and TEG parameters R and K (kinetic time), which reflect time to initial clot formation and speed of clot formation, respectively. Another study examining TEG in 270 patients with cirrhosis found that K, α-angle, and MA correlated well with platelet count and fibrinogen in all subgroups, regardless of cirrhosis etiology.…”
Section: Thromboelastographymentioning
confidence: 98%
“…Misperceptions of the bleeding risk in cirrhosis largely derive from clinicians' interpretation of standard coagulation tests, including prothrombin time (PT), international normalised ratio (INR), and activated partial thromboplastin time (APTT). However, as these conventional coagulation tests only provide a measure of procoagulant factors and are insensitive to the plasma levels of anticoagulant factors, they do not provide an accurate evaluation of the altered in-vivo haemostatic balance [2,12].…”
Section: Standard Coagulation Tests As a Measure Of Bleeding Risk In mentioning
confidence: 99%
“…VETs are increasingly being used as point-of-care tests to guide the rapid assessment and management of coagulopathies in trauma, surgery and liver transplantation. VETs provide a dynamic assessment of haemostasis, evaluating the kinetics of the entire coagulation process from initial clot formation to final clot strength, and provide a more comprehensive reflection of the interaction between plasma, blood cells and platelets [12].…”
Section: Standard Coagulation Tests As a Measure Of Bleeding Risk In mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the use of thromboelastography to predict thrombotic events in patients with ITP, we agree with Dr. Hill that more studies have to be performed to determine its utility in this field. Nevertheless, considering the value of thromboelastography for evaluating haemostasis in trauma patients (Veigas et al , ), major non‐cardiac surgery and liver disease (Shin et al , ) among other situations, we recommend its use to determine haemostasis in ITP patients with a sustained increase in platelet count.…”
mentioning
confidence: 99%